Chirp, squeal and dynamic instability of misaligned V-ribbed belts in automotive accessory belt drive systems. (5th July 2007) - Sheng, Gang; Brown, Les; Liu, Keming; Otremba, Jerzy; Pang, Jian; Qatu, Mohamad; Dukkipati, Rao
This paper presents a study of chirp, squeal and dynamic instability of V-ribbed (Micro-V™) belt under misalignment. In this study, historic results were reviewed and new experiments were conducted to investigate chirp generation mechanism. The new observations suggest that the chirp noise and dynamic instability are due to the friction-induced mode coupling of rib natural vibration modes. The investigation also suggests that the squeal noise, which takes place at some belt misalignment conditions, is a continuous chirp noise and shares the same features as individual chirp. A new mechanism of instability for radial rib slippage is proposed and used to correlate the experimental results with FEM results. A new mathematical model was used to illustrate the concept. It was shown that the friction-induced coupling of vibrational mode of slip rib results in mathematically unbounded oscillation solution with identical frequency. This illustrates the feature of identical frequency and harmonic oscillation dominating chirp and squeal noise. The proposed mechanism and model are expected to provide belt power transmission drive designers with new insight into the issues associated with improving the misaligned belt vibration and noise performance.